Pengaruh Etos Kerja Terhadap Kinerja Guru dan Dampaknya Terhadap Prestasi Belajar Siswa di SMP Muhammadiyah 1 Jember - Abdul Hamid Bakir; Bahar Agus Setiawan (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
Education which constitutes a conscious effort and is mandated by a constitution not only aims at developing intellectual but also spiritual aspects of individual students. Educational processes thus need to be built upon the work ethic so as to maximize teacher’s performance and to foster students’ learning outcomes. With this mind, the current study was conducted to examine whether the work ethic affected teacher’s performance and students’ achievement. This study employed a quantitative methodology and was conducted at SMP Muhammadiyah 1 Jember. The data were collected using a questionnaire, and were analyzed through a path analysis using Lisrel. The results revealed that the work ethic affected performance with a T value of 2.26 ≥ 1.196, the performance affected students’ achievement with a T value of 2.16 ≥ 1.196, but the work ethic did not affect students’ achievement as indicated by the T value. smaller than 1.96 of 0.56.